Optimal correction of distinct CFTR folding mutants in rectal cystic fibrosis organoids. Issue 2 (21st April 2016) - Dekkers, Johanna F.; Gogorza Gondra, Ricardo A.; Kruisselbrink, Evelien; Vonk, Annelotte M.; Janssens, Hettie M.; de Winter-de Groot, Karin M.; van der Ent, Cornelis K.; Beekman, Jeffrey M.
Small-molecule therapies that restore defects in cystic fibrosis transmembrane conductance regulator (CFTR) gating (potentiators) or trafficking (correctors) are being developed for cystic fibrosis (CF) in a mutation-specific fashion. Options for pharmacological correction of CFTR-p.Phe508del (F508del) are being extensively studied but correction of other trafficking mutants that may also benefit from corrector treatment remains largely unknown. We studied correction of the folding mutants CFTR-p.Phe508del, -p.Ala455Glu (A455E) and -p.Asn1303Lys (N1303K) by VX-809 and 18 other correctors (C1–C18) using a functional CFTR assay in human intestinal CF organoids. Function of both CFTR-p.Phe508del and -p.Ala455Glu was enhanced by a variety of correctors but no residual or corrector-induced activity was associated with CFTR-p.Asn1303Lys. Importantly, VX-809-induced correction was most dominant for CFTR-p.Phe508del, while correction of CFTR-p.Ala455Glu was highest by a subgroup of compounds called bithiazoles (C4, C13, C14 and C17) and C5. These data support the development of mutation-specific correctors for optimal treatment of different CFTR trafficking mutants, and identify C5 and bithiazoles as the most promising compounds for correction of CFTR-p.Ala455Glu. CFTR corrector efficacy selectively depends on the type of folding and trafficking mutation http://ow.ly/ZrrzB